Renovation, market economy and modernisation: Experiences from Northern Rural Vietnam - Van Suu, Nguyen (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Renovation, market economy and modernisation: Experiences from Northern Rural Vietnam(Lam Minh Chau. Ha Noi Publishing House. 2017. ISBN: 078-604-55-2241-7) This book uses the case of Vietnam to explore the experiences of rural people living in the aftermath of one of the greatest of the 20th century’s key social and economic transformations: the transition from socialist to marketised economic systems in Asia and beyond. The author conducted fieldwork in Xuan, a village in lowland Northern Vietnam, an area hitherto under-represented in the anthropological literature on post-socialist marketisation. Building on 15 months of fieldwork, I explore the highly diverse livelihood strategies of Xuan households as they have experienced the challenges and opportunities of Renovation (Đổi mới), Vietnam’s distinctive form of market opening launched in 1986. The state’s key goal under Renovation has been to override what is now stigmatised as ‘peasant’ thinking about risk-avoidance and excessive caution in livelihood choices, in favour of a vision of the countryside as a place of prospering commercial farmers plus a residual population committed either to commercial entrepreneurship or wage labour in a host of new local enterprises.In exploration of Xuan households’ Renovation experiences, author's focus is the local notion of đa gi năng. In pursuit of đa gi năng, Xuan households have embraced almost every market initiative that state officials have sought to implement under Renovation. At the same time, most have also maintained a diverse portfolio of small-scale livelihoods, thus evading what state modernisation advocates want most: commitment of householders’ whole resources into a single growth-oriented enterprise. Author's concern is thus with the sense Xuan households make of this mismatch between their decisions and the priorities set out by the state, as well as the means by which they have nevertheless sustained and even enhanced their families’ living standards.  The book seeks to contribute in two key ways to the anthropology of socialism/ post-socialism. First, the author argue that Xuan households practice đa gi năng because they have experienced Renovation as full of uncertainties of a relatively under-theorised kind. For them uncertainty is a permanent state rather than a provisional condition of early market reforms, and is felt by even the richest families rather than only by the poor majority. Yet the uncertain environment of Renovation also contains opportunities for improvements to families’ living conditions rather than merely dangers and destruction as many anthropologists have argued about market reforms in post-socialist Eastern Europe. Second, instead of fitting a single universal model, either ‘moral economy,’ ‘rational peasant,’ or the ‘structural inequality in access’ approach used by many Marxist scholars, Xuan households’ pursuit of đa gi năng is inspired by a locally specific dynamic: the concern for family security acted on in the light of a constant balancing of risk and opportunity. This dynamic motivates Xuan villagers to reflect at all times on the unpredictable nature of the market economy and state policies and their implications for family well-being, and make active judgments about risks and gains. Villagers thus‘ predict the unpredictable’: i.e. pursue two goals at the same time, these being the protection of family security and the quest for ever-improving living standards, rather than prioritising one at the expense of the other.